2014
DOI: 10.4137/tui.s13966
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Smoking among Bus Drivers of Dhaka, Bangladesh

Abstract: BACKGROUNDSmoking is an increasingly prevalent habit in Bangladesh, particularly among men with low socioeconomic status.AIMThe aim of this study was determining the prevalence and pattern of smoking among bus drivers of Dhaka city, Bangladesh.METHODSA cross-sectional study was carried out from 15 to 26 March 2013 among four hundred bus drivers of Dhaka city, Bangladesh aged between 18 and 50 determining the prevalence, pattern, and socioeconomic determinants of smoking. Data were input into a pre-designed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…This finding is similar to the studies of Biglari et al (15) and Kouvonen et al (34), but contrary to those of Nyberg et al (22) and Cunradi et al (35) who reported a positive association. The relationship between occupational stress and smoking could be explained by the fact that bus drivers feel it is a way to relieve tension (36) or as a result of neuroendocrine elevations associated with this stressful occupation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the studies of Biglari et al (15) and Kouvonen et al (34), but contrary to those of Nyberg et al (22) and Cunradi et al (35) who reported a positive association. The relationship between occupational stress and smoking could be explained by the fact that bus drivers feel it is a way to relieve tension (36) or as a result of neuroendocrine elevations associated with this stressful occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and occupational stress and hectic work schedules have been reported as reasons for smoking tobacco among bus drivers in Dhaka, Bangladesh. 13 Another important reason mentioned is to pass time during waiting hours for which education programmes to focus their attention somewhere else (e.g. mobile-phone games) can be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of developing countries (as the case of Colombia), a considerably minor amount of evidence has been accumulated regarding the impact of substance consumption upon subsequent health and safety outcomes among professional drivers [60,61] and its relationship with working conditions and job stress, even considering the typical adverse working conditions and high prevalence of addictive behaviors and Job Strain registered among professional drivers [8,53,62]. On the other hand, the existing empirical evidence about alcohol and tobacco consumption has addressed different factors modulating the impact of psychosocial factors at work, almost always in the form of increased health and accident risk, as well as with a higher prevalence of risky behaviors at the wheel.…”
Section: Discussionmentioning
confidence: 99%